2021
DOI: 10.3390/cells10061447
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Functions of Autophagy in Breast Cancer Development and Treatment

Abstract: Macroautophagy (herein referred to as autophagy) is a complex catabolic process characterized by the formation of double-membrane vesicles called autophagosomes. During this process, autophagosomes engulf and deliver their intracellular content to lysosomes, where they are degraded by hydrolytic enzymes. Thereby, autophagy provides energy and building blocks to maintain cellular homeostasis and represents a dynamic recycling mechanism. Importantly, the clearance of damaged organelles and aggregated molecules b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 206 publications
1
39
0
Order By: Relevance
“…Namely, autophagy is a pivotal process in control of cell fate and significantly correlates with apoptosis via inactivating the mammalian target of rapamycin (mTOR) signaling pathway or directly activates the initiation step of autophagy by phosphorylating unc-51-like autophagy activating kinase 1 (ULK1). In terms of cancer initiation, autophagy is considered tumor-suppressive due to its cytoprotective role (23,25,39,40). Notably, Marsh et al (25) discovered autophagy could inhibit the metastasis of BC cells by accumulating the autophagy cargo receptor (ACR), neighbor to BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, autophagy is a pivotal process in control of cell fate and significantly correlates with apoptosis via inactivating the mammalian target of rapamycin (mTOR) signaling pathway or directly activates the initiation step of autophagy by phosphorylating unc-51-like autophagy activating kinase 1 (ULK1). In terms of cancer initiation, autophagy is considered tumor-suppressive due to its cytoprotective role (23,25,39,40). Notably, Marsh et al (25) discovered autophagy could inhibit the metastasis of BC cells by accumulating the autophagy cargo receptor (ACR), neighbor to BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…The role of autophagy in cancer in general and in breast cancer in particular is emerging [ 43 , 44 , 45 ]. Regulation of autophagy is considered a method to prevent breast cancer and break therapeutic resistance (reviewed in [ 46 ]). It was shown that the vitamin D/VDR axis in breast cancer is regulated by many miRNAs [ 47 ].…”
Section: Vitamin D Signaling In Breast Cancermentioning
confidence: 99%
“…BC is immensely heterogeneous with diverse histopathological properties and molecular profiles. From a molecular viewpoint, 4 distinct BC subtypes have been identified including luminal A, luminal B, human epidermal growth factor receptor 2 positive (HER2+), and triple-negative [4,5]. In addition, BC can be categorised into immunohistological subtypes based on oestrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status.…”
Section: The Molecular Characteristics Of Dormant Breast Cancer Cellsmentioning
confidence: 99%